1990
DOI: 10.1146/annurev.pa.30.040190.001011
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Opioid Receptors

Abstract: Though opioid receptors are more difficult to purify and characterize than other cell surface receptors, significant progress has been made in the past several years. At least a dozen groups have now reported purification of opioid-binding proteins, either in a form that retains ligand-binding properties, or in a covalently bound form. Although there are some discrepancies in the molecular weights of these proteins, it is significant that many investigators have reported a molecular weight of about 60 kd for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
72
0
1

Year Published

1993
1993
2007
2007

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 249 publications
(76 citation statements)
references
References 0 publications
3
72
0
1
Order By: Relevance
“…In the current study, we show that galanin receptor levels do not change significantly during chronic morphine treatment alone. Previous studies have shown that opioid receptor levels are also unchanged by this treatment (Loh and Smith 1990). In contrast, 5 h following naltrexone-precipitated withdrawal, galanin receptor binding increased by approximately 150%, and GalR1 mRNA levels increased approximately 120%.…”
Section: Discussionmentioning
confidence: 69%
“…In the current study, we show that galanin receptor levels do not change significantly during chronic morphine treatment alone. Previous studies have shown that opioid receptor levels are also unchanged by this treatment (Loh and Smith 1990). In contrast, 5 h following naltrexone-precipitated withdrawal, galanin receptor binding increased by approximately 150%, and GalR1 mRNA levels increased approximately 120%.…”
Section: Discussionmentioning
confidence: 69%
“…Galanin, opioid, and DA receptors are GPCRs that modulate many signaling pathways including those involving ERK1/2 (Belcheva et al, 2005(Belcheva et al, , 2001Hawes et al, 2006a;Loh and Smith, 1990;Williams et al, 2001). Chronic morphine exposure (Berhow et al, 1996) and stimulation of several GPCRs, including opioid receptors, leads to ERK activation in the VTA (Eitan et al, 2003) and inhibition of ERK activity in the VTA suppresses the rewarding effects of morphine (Ozaki et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In neuronal cells, morphine binds to a G protein-coupled -opioid receptor to induce analgesia (9,10). Activation of the -opioid receptor leads to regulation of several intracellular effectors, such as modulation of adenylyl cyclase activity (11).…”
mentioning
confidence: 99%